Improving of Organic Fertilizers Quality from Sludge Water Treatment plant Compost by IMOs with the Different Material Combination - PHOMMALINH, Kolakoth; BOUNKHOUN , Khamchan; VANASY, Syphachanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The organic farming is a good alternative option for the farmer and organic fertilizer is also the important factor in doing the organic farming, especially the quality fertilizer. In this research was conducted the experiment on the use of Indigenous Microorganisms (IMO) to improve the quality of organic fertilizers made from wastewater treatment sludge of Lao Brewery factory with the different combination of ingredients. The CRD research model has been used in this research which comprises 3 Replication (R) in 5 Treatment (T) and having 30 days fermented. The sample has been examined in the laboratory to find out the chemical qualities and production cost assessment. The result showed that, the IMOs microorganisms plays the important role in improvement the quality of organic fertilizer. Including organic matter (OM) was increased from 20.97% – 47.42% and potassium (K) was also increased from 0.08 % - 1.21% (in comparison with the control treatment). The high quality of organic fertilizer based on chemical and physical properties was T5 which combine sludge, rice’s bran, cow dung, mashed grass and IMO. A laboratory result of composed fertilizer using IMOs showed that the N values was 1.92%, P values was 3.23%, K values was 1.21%, OM values was 47.42% and pH values was 8.0. It was high when compares with the quality standards of organic fertilizers of the Department of Horticulture, Ministry of Agriculture and Forestry as well as it was low cost. However, this research suggests that the sludge shall be mixed with the waste likes cow dung and grass in order to reduce the sludge's freeze-drying problem as well as to improving of Potassium (K), Phosphorus (P) nutrition. Thus, the promotion of using wastewater treatment sludge of Lao Brewery factory to produce the organic fertilizer is needed and microorganisms shall be used in the production processing since it is not only boost up the quality of the fertilizer, but it is also able to solve the environmental problems too.